Acceptability and efficacy of intra-rectal quinine alkaloids as a pre-transfer treatment of non-per os malaria in peripheral health care facilities in Mopti, Mali - Sacko Massambou; Coulibaly Drissa; Traoré Oumar B; Sissoko Mahamadou S; Keita Falaye; Thera Mahamadou A; Lameyre Valerie; Ducret Jean; Doumbo Ogobara (Malaria Journal, 2007)
Abstract Background The acceptability and efficacy of a new kit with a new formulation of quinine alkaloids designed for the intra-rectal administration in the treatment of non-per os malaria was assessed in the peripheral health care system of Mopti, Mali. Methods A single-arm trial was conducted from August 2003 to January 2004. An initial dose of diluted quinine alkaloids (20 mg/kg Quinimax®) was administered by the intra-rectal route to children with presumptive non per-os malaria at six peripheral heath care centres. The children were then referred to two referral hospitals where standard inpatient care including intravenous route were routinely provided. A malaria thick smear was done at inclusion and a second malaria thick smear after arrival at the referral facility, where a more complete clinical examination and laboratory testing was done to confirm diagnosis. Confirmed cases of severe malaria or others diseases were treated according to national treatment guidelines. Cases of non per-os malaria received a second dose of intra rectal quinine alkaloids. Primary outcome was acceptability of the intra rectal route by children and their parents as well as the ease to handle the kit by health care workers. Results The study included 134 children with a median age of 33 months and 53.7% were male. Most of the children (67%) and 92% of parents or guardians readily accepted the intra-rectal route; 84% of health care workers found the kit easy to use. At the peripheral health care centres, 32% of children had a coma score ≤ 3 and this was reduced to 10% at the referral hospital, following one dose of intra-rectal quinine alkaloids (IRQA). The mean time to availability of oral route treatment was 1.8 ± 1.1 days. Overall, 73% of cases were confirmed severe malaria and for those the case fatality rate was 7.2%. Conclusion IRQA was well accepted by children, their parents/guardians and by the health workers at peripheral health facilities in Mopti, Mali. There was also a quick recovery from deep coma and a reduced case fatality rate in severe malaria.